Prevalence Of Noise Induced Hearing Loss Among Kitchen Staff In Malaysia East Coast Hospital - Hui, Lo Ren (2020)
Introduction: Noise can be hazardous as it is known to cause hearing loss. Since the industrial revolution, various factories or large scale set up are known to produce excessive noise. Kitchen especially hospital kitchen is one of it that produce tremendous noise pollution. Long hours of working in hospital kitchen may potentially lead to hearing loss. Objective: To study on noise induced hearing loss (NIHL) among hospital kitchen staff compare to other staff in East Coast Malaysia Hospitals. Methodology: This was a descriptive cross-sectional study. The source population was from kitchen staffs of 5 Malaysian East Coast Hospitals comparing to other hospital staffs (hospital clerk, clinical based medical attendant) of the same hospitals. The data were collected at these 5 hospitals, outpatient clinics to fill the pro forma, otoscopic examination and hearing test using pure tone audiometry in a soundproof room at least 48 hours after the subjects were free from noise exposure. Results: A total of 123 hospital kitchen staffs and 122 other hospital staffs participated in this study. There was a significant correlation of noise induced hearing among the hospital kitchen staffs (54.3%) compared to the other group (27%). The dip on pure tone audiometry was mostly at 6kHz, followed by 4kHz and 3 kHz. There was a significant mean difference of years of service between groups (mild, moderate, severe) of hearing impairment (p=0.010). Conclusion: This study showed that hospital kitchen noise is hazardous to its working staffs that working. Kitchen staffs will have a worse hearing loss following longer term of working years. We recommend all hospital kitchen staffs the use of hearing protection equipment while working in the kitchen.